P265 Maxillomandibular Advancement Surgery in the Management of Obstructive Sleep Apnoea. (19th November 2012) - Patel, Meera; Gurney, B; Daley, D; Marshall, K; McAllister, W; Haers, P
Abstract : Introduction: Obstructive sleep apnoea (OSA) is a clinical condition in which there is intermittent and repeated upper airway collapse during sleep. Maxillomandibular advancement (MMA) has been shown to enlarge the pharyngeal and hypopharyngeal airway by physically expanding the facial skeletal framework. It has also been shown that advancement of the maxillomandibular complex increases tissue tension, and is a valid surgical treatment option for those patients unable or unwilling to tolerate long term continuous positive pressure ventilation (CPAP). Method: We present a series of 10 patients who underwent MMA and genioplasty surgery for OSA, operated by one surgeon, with an average age of 47 years and an average BMI of 27. The minimum advancement of the mandible was 15mm with the maxilla advancing between 12–15 mm. Diagnosis of OSA was based on: clinical history, Epworth Sleepiness Scale (ESS) questionnaire, and formal sleep study parameters via ambulatory sleep study. Lateral cepalometric radiographs were taken pre- and post-operatively to assess widening of the posterior airway space (PAS). The patients were reassessed using the same criteria 6 months post surgery, with annual follow up. Results: All 10 patients reported an improved ESS with the average reduction of 70.3%. The PAS increased by 48.4% (5.11mm), on average, with the biggest increase recorded as 11.8mm. The average apnoea hypopnoea index and oxygen desaturation events decreased by 74% and 69% respectively. Conclusion: The outcome of MMA advancement has previously been reported, with success rates in the literature varying from 57% to 100%. There are no long term studies indicating success. The outcomes of our series of patients support MMA advancement as an effective surgical treatment for OSA and show sustained improvement up to 5 years postoperatively. Careful patient selection and a multidisciplinary approach to management are key to achieving success. Although CPAP remains the standard treatment for most patients with OSA, MMA provides an alternative for selected OSA patients who cannot use CPAP or who wish a curative treatment without life-long dependency on these devices.